Multi-biochemical responses of benthic macroinvertebrate species as a complementary tool to diagnose the cause of community impairment in polluted rivers - Damasio, J
Biological indexes, based on benthic macroinvertebrate taxa, are currently used worldwide to measure river ecological quality. These indexes assign a global ecological status of the biotic community, but not necessarily may detect specific effects of water pollutants. Conversely a large set of biochemical markers measured in macroinvertebrate benthic species can detect sublethal effects and inform us about additional environmental factors that are impairing benthic communities. This is especially interesting in moderately polluted sites, where other stressors are already affecting communities but not too strongly to be detected by biotic indexes. Up to ten different markers belonging to distinct metabolic paths and 42 contaminants measured in sample collections of the caddis fly Hydropsyche exocellata were assessed across a polluted gradient in the industrialized Mediterranean River basins of Besos and Llobregat (NE, Spain). Twenty four sample collections were selected to include macroinvertebrate communities representing the five impairment degrees defined by the Spanish Environmental authorities using the biotic metrics. Results evidenced a clear deterioration of the ecological water quality parameters and benthic communities towards downstream reaches. Biochemical responses varied significantly across the studied samples and were able to differentiate samples within communities having a good and deteriorated ecological stage. Principal Component Analyses indicated that salinity was one of the major stresses affecting macroinvertebrate assemblages, whereas antioxidant and metabolizing enzymes responded differently and were closely related to high and presumably toxic levels of accumulated organic pollutants. Therefore these results indicate that the use of multiple -markers sensitive to water pollution may provide complementary information to diagnose environmental factors that are impairing macroinvertebrate communities. (C) 2011 Elsevier Ltd. All rights reserved.